2013
DOI: 10.4319/lo.2013.58.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volcanic eruption on nutrients, light, and phytoplankton in oligotrophic lakes

Abstract: Volcanic eruptions that shape the earth's surface can have major effect on ecosystems and, as natural

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 47 publications
1
51
1
14
Order By: Relevance
“…This study agrees with previous studies carried out in lakes of northern Patagonia, which evaluated the effect of recent eruption of these events on lake productivity (Modenutti et al 2013;Balseiro et al 2014) and on the mechanical impact of the ash deposition on chironomid communities (Massaferro et al 2005;Araneda et al 2007;Serra et al 2016, Williams et al 2016). However, rising temperatures of the last 50 years, and the increase in human activities also caused environmental changes that enhanced lake productivity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study agrees with previous studies carried out in lakes of northern Patagonia, which evaluated the effect of recent eruption of these events on lake productivity (Modenutti et al 2013;Balseiro et al 2014) and on the mechanical impact of the ash deposition on chironomid communities (Massaferro et al 2005;Araneda et al 2007;Serra et al 2016, Williams et al 2016). However, rising temperatures of the last 50 years, and the increase in human activities also caused environmental changes that enhanced lake productivity.…”
Section: Discussionsupporting
confidence: 92%
“…Parapsectrocladius inhabits littoral areas and it has been recorded in sediments immediately after exogenic disturbances (Massaferro and Brooks 2002). Balseiro et al (2014) and Modenutti et al (2013) evaluated the impact the 2011 eruption of Caulle/Puyehue volcanoes on the lake dynamics in northern Patagonia. Both studies showed that tephra deposition in lakes enhances the growth of the phytoplankton community and the increase of chlorophyll derivatives due to the reduction of photo inhibition and increased phosphorus concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison of pumice nutrient uptake rates to microplankton nutrient demand in the mixed layer of Lake Espejo, we used experimental (10) and monitoring data from mid-January 2012 (specific growth rate of 0.1 day Ϫ1 and overall seston biomass in the upper mixed layer [4-m depth] of ϳ3.2 ϫ 10 4 mol C m Ϫ2 with C/N/P ratios of 135:9:1 [molar]) (10). Multiplying the specific growth rate by C biomass per unit area and then this value by the observed seston N/C and P/C ratios yielded rates of microplankton N and P demand of 24 mol P m Ϫ2 day Ϫ1 and 210 mol N m Ϫ2 day Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…1A). We earlier reported the effects of suspended ash on limnological conditions in the lakes impacted by PuyehueCordón Caulle (10). Here we focus not on the ecological impacts of the eruption in the lakes per se but instead on the emergence of unique and largely unstudied novel habitats that followed the eruption: large, island-like aggregations of floating pumice rocks (0.1 to 5 cm in diameter) ( Fig.…”
mentioning
confidence: 99%